2017
DOI: 10.31018/jans.v9i4.1544
|View full text |Cite
|
Sign up to set email alerts
|

Boron availability in relation to some important soil chemical properties in acid soils of Cooch Behar district, West Bengal

Abstract: In the present study, we investigated the distribution of soil available boron and its relationship with some soil properties in the samples collected from different locations in acidic alluvial soils of Cooch Behar district in West Bengal during 2013-2014. For the study about two hundred fifty (250) georeferenced surface soil samples covering 11 blocks of the districts were collected with the help of a global positioning system (GPS). The soil results revealed that pH of the analyzed samples varied from 4.91-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They discovered a strong link between accessible B content, EC, pH, and organic carbon concentration [41]. In the pH range of 3 to 9, boron adsorption by soils increased, but in the pH range of 10 to 11.5, it declined [42,43] observed that B adsorption was influenced by soil qualities such as organic matter, clay, and aluminium oxide content, and that it was reliant on and increased as a function of pH. The impact of organic matter on the availability of B in soils is magnified as the pH and clay content of the soil rise.…”
Section: Availability Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered a strong link between accessible B content, EC, pH, and organic carbon concentration [41]. In the pH range of 3 to 9, boron adsorption by soils increased, but in the pH range of 10 to 11.5, it declined [42,43] observed that B adsorption was influenced by soil qualities such as organic matter, clay, and aluminium oxide content, and that it was reliant on and increased as a function of pH. The impact of organic matter on the availability of B in soils is magnified as the pH and clay content of the soil rise.…”
Section: Availability Of Bmentioning
confidence: 99%
“…This increase could be due to the decomposition of organic matter which produces acids such as tartaric, oxalic, citric, acetic, formic, and humic acid, which solubilized the unavailable fixed B in clay or CaCO 3 . Furthermore, some B gets complexed or chealeted with organic mattercontent and this B is released into the soil solution as the organic matter decomposes [42].Because minimal B adsorption on the mineral fraction occurs at low pH values, organic matter is one of the most important sources of B in acid soils [23].…”
Section: Availability Of Bmentioning
confidence: 99%
“…Its bioavailability decreases at a higher solution pH [ 8 ], which occurs mainly at pH values higher than 6, where B forms insoluble compounds with oxides of iron and aluminum [ 9 ]. High organic carbon content increases the availability of B for plants [ 10 ]. Owing to changes in rainfall patterns [ 11 ], there has been a decrease and increase in the availability of B in the soil, depending on the prevailing conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low soil fertility in sub-Sahara Africa is a major constraint limiting agricultural production, mainly caused by low inherent soil fertility, low use of fertilizers, soil acidity and continuous cropping without adequate nutrient replenishment (Henao and Baanante, 2006). Crop growth and productivity depend on nutrient availability which is primarily influenced by soil pH and organic matter concentration (Chianu et al, 2012;Kundu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%